Peningkatan Sistem Akuntansi dan Transparansi Keuangan pada UMKM Elok Mekar Sari di Surabaya - Irda Agustin Kustiwi; Nayve Ruben Jr; Zahra Choirunisa (CV. ALIM'SPUBLISHING, 2026)
MSMEs have a strategic role in supporting regional economic growth, but they still face many obstacles in financial management and the preparation of accountable financial statements. Elok Mekar Sari Surabaya MSMEs are one of the business actors that face limitations in the implementation of accounting systems and financial transparency. This community service activity aims to increase the understanding and ability of MSME actors in implementing a simple accounting system and strengthen transparency in business financial management. The method of implementing activities includes initial observation, identification of needs, training in recording financial transactions, assistance in the preparation of financial statements, and evaluation of activity results. The results of the service show an increase in partners' understanding of the importance of systematic transaction recording, separation of personal and business finances, and the preparation of more structured financial statements. In addition, partners are able to implement a simple financial recording system that supports transparency and business decision-making. This activity is expected to increase the accountability of financial management and support the sustainability of the MSME business of Elok Mekar Sari Surabaya.